Effect of nutrient management practices on crop growth and yield of maize (Zea mays L.) - Utkarsh Singh; Rajesh kumar; Sanjeev Singh; Abhinav Kumar; Anand Singh; Abhinandan Singh; Shipra Yadav; Anil Kumar Singh; Neeraj Kumar; Ajay Singh; et al. (The Bioscan, 2025)
The field experiment was conducted at the agronomy research farm of Acharya Narendra Deva University of Agriculture & Technology, Kumarganj, Ayodhya, Uttar Pradesh to access the effect of optimization of nutrient management practices on growth and yield of maize during kharif season of 2023 and 2024. The experiment was laid out in factorial randomized block design (FRBD) with 3 replications and consists three RDF Levels 50% RDF (NPK), 75% RDF (NPK) and 100% RDF (NPK)) and five Bio-agent enriched FYM and micronutrient (Zn @ 5 kg ha-1 + B @ 1kg ha-1, Enriched FYM @ 5 t ha-1, Enriched FYM @ 10 t ha-1, Zn @ 5 kg ha-1 + B @ 1kg ha-1 + Enriched FYM @ 5 t ha-1, Zn @ 5 kg ha-1 + B @ 1kg ha-1 + Enriched FYM @ 10 t ha-1). Results indicate that among the RDF levels crop fertilized with 100% RDF (NPK) recorded significantly highest plant height (96.76 & 99.36 cm, 176.24 & 180.98 cm and 205.88 & 211.38 cm), highest leaf area index (2.88 & 2.91, 4.18 & 4.23 and 3.34 & 3.38) at knee-high, tasseling and harvest stage of crop growth during 2023 and 2024, respectively. Similarly, maximum grain yield (43.20 & 44.94 q ha-1) was recorded under 100% RDF. Among the bio-agent enriched FYM and micronutrient application of Zn @ 5 kg ha-1 + B @ 1kg ha-1 + Enriched FYM @ 10 t ha-1) recorded significantly the highest plant height (95.93 & 98.50cm, 174.73 & 179.40 cm and 204.13 & 209.60 cm), highest leaf area index (2.84 & 2.87, 4.11 & 4.16 and 3.29 & 3.33) at knee-high, tasseling and harvest stage of crop growth during both the years of investigation. Similarly, maximum grain yield (47.12 & 49.02 q ha-1) was reported with same treatment.